Muscular coordination of the lower extremities of oarsmen during ergometer rowing - Janshen, L.; Mattes, K.; Tidow, G. (Journal of Applied Biomechanics, 2009)
In sweep-oar rowers, asymmetrical force production of the legs is a known phenomenon. The purpose of this study was to investigate the muscular activity of the legs that may cause this asymmetry even when oarsmen perform a symmetrical endurance task. Seven male young elite oarsmen performed an all-out 2000-m test on a rowing ergometer. During stroke kinematics, myoelectric activity of six muscles of each leg and pressure distribution under both feet were measured. Data were collected over two 30-s time windows starting 1 and 5 min after the test started. No significant differences were observed between legs and time windows for the range of motion of the hip, knee, and ankle joint as well as for the onset/offset timing of muscles. However, in the drive phase, the knee and hip muscles of the leg on the oar side (inside leg) showed 20-45% (both p < .05) higher activation intensities compared with the leg opposite the oar (outside leg). Corresponding to this, 56-91% (both p < .05) higher mean pressure values under the ball of the inside foot compared with the outside foot indicated an asymmetrical force production of the legs even under kinematically symmetrical working conditions.